2021
DOI: 10.1016/j.jcmgh.2020.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Distinct and Overlapping Roles of Hippo Effectors YAP and TAZ During Human and Mouse Hepatocarcinogenesis

Abstract: Background & Aims Yes-associated protein (YAP) and its paralog transcriptional co-activator with post synaptic density protein, drosophila disc large tumor suppressor and zonula occludens-1-binding motif (TAZ) are 2 co-activators downstream of Hippo tumor-suppressor cascade. Both have been implicated in the development of hepatocellular carcinoma (HCC). However, whether YAP and TAZ have distinct or overlapping functions during hepatocarcinogenesis remains unknown. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…In this context, YAP-dependent proliferation of liver cells is leading to the accumulation of mutations and the induction of chromosomal instability (CIN) [ 3 ]. However, the oncogenic role of TAZ in hepatocarcinogenesis is less defined, although previous results illustrated both tumor-initiating and tumor-supporting properties [ 6 , 7 ]. In addition, recent data demonstrated that TAZ cooperates with YAP in HCC progression [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, YAP-dependent proliferation of liver cells is leading to the accumulation of mutations and the induction of chromosomal instability (CIN) [ 3 ]. However, the oncogenic role of TAZ in hepatocarcinogenesis is less defined, although previous results illustrated both tumor-initiating and tumor-supporting properties [ 6 , 7 ]. In addition, recent data demonstrated that TAZ cooperates with YAP in HCC progression [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we showed that high SOX9 expression correlated with molecular pathways critical for HCC carcinogenesis (YAP-TAZ) 16,36. Very recent work has shown that SOX9 is required for Yap-induced hepatocyte plasticity during hepatocarcinogenesis in mice and, using transcriptomic profiling of 236 liver tumor samples from Japanese patients, YAP activity and SOX9 expression were found to be strongly correlated with liver tumor plasticity in human patients.…”
Section: Discussionmentioning
confidence: 73%
“…TAZ expression significantly correlates with aggressive HCC features, including tumor size, TNM stage, lymph node or distant metastasis, histological differentiation, recurrence, and poor prognosis [ 28 ]. Furthermore, forced overexpression of TAZ promotes cell proliferation, migration, and invasion of HCC cell lines in vitro , whereas opposite effects accompany TAZ knockdown [ 28 , 29 ]. In iCCA, recent studies indicate that TAZ expression is more pronounced in tumor tissues than in the peritumoral counterpart [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%